2018
DOI: 10.1016/j.scitotenv.2017.10.139
|View full text |Cite
|
Sign up to set email alerts
|

Riverine phytoplankton shifting along a lentic-lotic continuum under hydrological, physiochemical conditions and species dispersal

Abstract: The importance of phytoplankton-based bio-assessment has been recently recognized in lowland rivers which are affected by multi-environmental factors. However, some basic questions remain unclear to date, such as: (i) spatial and temporal variations of phytoplankton, (ii) the impact of upstream lakes on downstream community, (iii) the main drivers for species composition or (iv) the regional biodiversity along a lentic-lotic continuum. To answer these questions, we collected and analyzed the fluvial phytoplank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 82 publications
4
22
0
1
Order By: Relevance
“…A previous study on the relations among 83 hydrological metrics and changes in algal communities of the United States was consistent with our study and demonstrated the importance of hydrological variables to the variance of specific algal community metrics (Steuer, Stensvold, & Gregory, ). Moreover, recent studies (Qu et al., ; Wu et al., ), which were in line with our finding, also found that hydrological conditions played an important role in temporal variations of pelagic algae communities. Skewness of flows was found to be one of the most consistently dominant indices across all stream types and may be a particularly important measure of flow condition for certain riverine taxa (Olden & Poff, ), for example, annual skewness of the flow has been linked to fish mobility and colonizing ability (Puckridge, Sheldon, Walker, & Boulton, ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A previous study on the relations among 83 hydrological metrics and changes in algal communities of the United States was consistent with our study and demonstrated the importance of hydrological variables to the variance of specific algal community metrics (Steuer, Stensvold, & Gregory, ). Moreover, recent studies (Qu et al., ; Wu et al., ), which were in line with our finding, also found that hydrological conditions played an important role in temporal variations of pelagic algae communities. Skewness of flows was found to be one of the most consistently dominant indices across all stream types and may be a particularly important measure of flow condition for certain riverine taxa (Olden & Poff, ), for example, annual skewness of the flow has been linked to fish mobility and colonizing ability (Puckridge, Sheldon, Walker, & Boulton, ).…”
Section: Discussionsupporting
confidence: 93%
“…Our results in this study showed that the pelagic community in Treene catchment was more affected by local effects (e.g., local hydrological and environmental variables) than spatial effects as indicated by spatial variables (Figure ). These findings supported the recent studies (Qu et al., ; Wu et al., ) and further emphasized the suitability of lowland pelagic algae as bioindicator for local habitat changes. Nevertheless, factors such as interaction between organisms (niche competition), dispersal ability, and species evolution, which were not considered in this study, may have reduced the explainable variations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In particular, macroinvertebrates have evolved distinct adaptations to flow conditions and hence are affected by their changes (Domisch et al, ). These dependencies on flow have been used frequently to assess the occurrence (Pyne & Poff, ) and diversity (Poff & Zimmerman, ) of riverine species, such as fish (O'Keeffe et al, ), benthic invertebrates (Armanini, Horrigan, Monk, Peters, & Baird, ), or phytoplankton (Qu, Wu, Guse, & Fohrer, ), using microcosm experiments (Ceola et al, ), statistical models (Kakouei et al, ), or process‐based models (Mondy & Schuwirth, ). In the absence of direct measurement data or for scenario assessments, modelled streamflow is often used as a data basis for such analysis.…”
Section: Introductionmentioning
confidence: 99%
“…TB were dominant in most of the study area, while their share varied in time and space (Qu et al, 2018b). The temporary intensive occurrence of Microcystis in dry season received high concerns from the local stakeholders (Qu et al, 2018a). Therefore, we are especially interested in these two functional groups TB and M, in addition to the phytoplankton community characteristics.…”
Section: Introductionmentioning
confidence: 99%